2003
DOI: 10.1159/000068160
|View full text |Cite
|
Sign up to set email alerts
|

Patient Satisfaction with Three Dental Speciality Services: A Centre-Based Study

Abstract: Objective: To assess the level of patient satisfaction with three dental speciality services: oral surgery, periodontics, and fixed prosthodontics. Subjects and Methods: A sample of 1,242 patients, aged 16 years and over who received dental care at least twice at the main dental centre, Al-Amiri, Kuwait, were interviewed during May–August 1998 by independent researchers concerning their experience of previous visits. Patients reported their level of satisfaction on a 5-point Likert scale for the items in the q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 12 publications
2
25
0
4
Order By: Relevance
“…Cost of care has also been shown to have a negative effect on patient satisfaction among adults in Sweden (22). The low levels of satisfaction with explanation of treatment reported in the present study were similar to those reported in the United Arab Emirates (20) and Kuwait (25). In this study, one of the explanations for the very low satisfaction with treatment cost might have been that cost sharing in health is a relatively new concept among Tanzanians.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Cost of care has also been shown to have a negative effect on patient satisfaction among adults in Sweden (22). The low levels of satisfaction with explanation of treatment reported in the present study were similar to those reported in the United Arab Emirates (20) and Kuwait (25). In this study, one of the explanations for the very low satisfaction with treatment cost might have been that cost sharing in health is a relatively new concept among Tanzanians.…”
Section: Discussionsupporting
confidence: 84%
“…High levels of patient satisfaction have been reported in different countries (20)(21)(22)(23), and the most important factors influencing this have included cost, waiting time, care organisation and reception (22), belief about the care received and the environment of care (24), communication skills and structural aspects of the clinic (25), belief in the dentist, and pain control (26). In Sweden, Riley et al (27) indicated that rural respondents were less likely to be satisfied with dental care than urban respondents, and that male young adults were more likely to report satisfaction than young female adults (26).…”
Section: Introductionmentioning
confidence: 99%
“…Waiting time is an important quality indicator in measuring the outcome of any medical service. Extended waiting time at the dental clinic and substantial delay in receiving the needed care had resulted in patient dissatisfaction with the care provided [29,30]. For most mothers in this study, time was an important essence as reflected in their responses that they were busy either at work or running the household chores.…”
Section: Discussionmentioning
confidence: 99%
“…This is in concordance with several studies reporting that waiting time was the least satisfactory issue. [15–18] Dissatisfaction with waiting time in the clinic reveals an important problem that needs to be resolved, possibly through limiting the number of patients to reduce the waiting time. [15] But it is difficult to apply in this hospital, as the number of patients in need of dental treatment are quite high.…”
Section: Discussionmentioning
confidence: 99%
“…[15–18] Dissatisfaction with waiting time in the clinic reveals an important problem that needs to be resolved, possibly through limiting the number of patients to reduce the waiting time. [15] But it is difficult to apply in this hospital, as the number of patients in need of dental treatment are quite high. The possible way to solve the problem is by increasing the numbers of dental staff in the polyclinic, as well as the dental chairs.…”
Section: Discussionmentioning
confidence: 99%